Intra-seasonal rainfall variability and crop yield in the Upper East Region of Ghana - Adimassu, Zenebe; Mul, Marloes; Owusu, Afua (Springer, 2024)
Occurrence of frequent dryspell is affecting agriculture; productivity in the semi-arid areas of West Africa such as northern Ghana. The objective of this study was to analyze the effects of dryspells on rainfed maize (early and late maturing), millet, and sorghum yields in a savanna agro-ecosystem in northern Ghana, and suggest management options for reducing their impacts. Long-term dryspell analyses were carried out using INSTAT + v3.37 on climatic data collected over a 30- to 50-year period. The probabilities of dryspells exceeding 7, 10, 14 and 21 days were calculated for crop types during different physiological growth stages and growing seasons of varying lengths. CROPWAT 8.0 was used to determine effective rainfall, crop water requirement, crop water deficit, and changes in yield. The results showed that 80% of the rains begin between the second week of May and the third week of June in the Upper East Region of Ghana. The result also revealed that more dryspells occurred after the initial growth stage of crops. During mid and late stages of crop growth there was a 50% probability of dryspells greater than seven days for early maturing maize and millet and of > 70% for sorghum. Late maturing maize experienced higher crop water deficit than early maturing maize. The result also showed that significant yield reduction (36% reduction in late maturing maize at both Navrongo and Zuarungu) occurs if planting is done before May 21. Similarly, 25 and 23% yield losses, were observed in sorghum at Navrongo and Zuarungu, respectively. We therefore recommend (i) early maturing crop varieties, (ii) adjusting sowing dates based on seasonal climate information, and (iii) improving water management.